2021
DOI: 10.4038/jbt.v5i2.29
|View full text |Cite
|
Sign up to set email alerts
|

Trust Repair Efforts and Repurchase Intention after Negative Publicity of Milk Powder in Sri Lanka

Abstract: This paper aimed to examine the impact of trust repair efforts on consumers repurchase intention of milk powder products affected by negative publicity in Sri Lanka. Consumer response to business entity's effort to mitigate negative information are understudied in developing economies including Sri Lanka. A quantitative survey design was opted for this study. Data was collected from 140 consumers residing in the western province of Sri Lanka employing a questionnaire during the pandemic. The proposed hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In addition, high population pressure of developing countries demands importation of milk powder that incurs high risk. For instance, laboratory tests conducted using several imported milk powder brands in Sri Lanka confirmed that four of the tested brands were contaminated with dicyandiamide (DCD) that alarms the risk of importation (Ranasinghe and Shamil, 2021). At present, Sri Lankan consumers' preference for milk powder brands has been changed showing a high inclination towards local milk powder brands owing to the disputable information released via mass media (Economic and Social Statistics of Sri Lanka, 2018).…”
Section: Consumer Health Consciousness and Brand Loyaltymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, high population pressure of developing countries demands importation of milk powder that incurs high risk. For instance, laboratory tests conducted using several imported milk powder brands in Sri Lanka confirmed that four of the tested brands were contaminated with dicyandiamide (DCD) that alarms the risk of importation (Ranasinghe and Shamil, 2021). At present, Sri Lankan consumers' preference for milk powder brands has been changed showing a high inclination towards local milk powder brands owing to the disputable information released via mass media (Economic and Social Statistics of Sri Lanka, 2018).…”
Section: Consumer Health Consciousness and Brand Loyaltymentioning
confidence: 99%
“…Due to self-insufficiency in milk production, Sri Lanka depends to a large extent on imported milk powder from countries such as Australia and New Zealand (Gunarathne et al, 2015;Krishnapillai et al, 2020;Wijesinghe et al, 2021). Owing to that, the annual importation of milk powder to Sri Lanka amounts hundred thousand metric tons in order to meet the consumption requirement of the country (Ranasinghe and Shamil, 2021). However, the quality and the safety of imported milk powder had been questioned in several occasions during the past decade (Stewart, 2021;Wijesinghe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic milk production in Sri Lanka meets only about 38% of the national requirement (Central Bank, 2019). Hence, milk products, primarily in the form of powdered milk, are imported to Sri Lanka (Ranasinghe and Shamil, 2021). As a result, per capita consumption of milk powder in Sri Lanka exceeds that of liquid milk.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has recently been found that imported milk powder has been contaminated with hazardous chemicals and foreign fats that create a threat to human lives (Wijesinghe et al, 2020). In 2014, a famous New Zealand company that operated in Sri Lanka faced a crisis of detection of dicyandiamide in their milk powder (Ranasinghe and Shamil, 2021). Therefore, on one hand, this study helps to better focus on significant marketing mix antecedents attached to powdered milk brand preference from consumers' point of view, and on the other hand, it may support the development of the social and economic status of the domestic producers.…”
Section: Introductionmentioning
confidence: 99%